Shared auditors in mergers and acquisitions - Dhaliwal, Dan S.; Lamoreaux, Phillip T.; Litov, Lubomir P.; Neyland, Jordan B. (Journal of Accounting and Economics, 2016)
We examine the impact of shared auditors, defined as audit firms that provide audit services to a target and its acquirer firm prior to an acquisition, on transaction outcomes. We find shared auditors are observed in nearly a quarter of all public acquisitions and targets are more likely to receive a bid from a firm that has the same auditor. Moreover, these shared auditor deals are associated with significantly lower deal premiums, lower target event returns, higher bidder event returns, and higher deal completion rates. These results are driven by bids in which targets and acquirers share the same practice office of an audit firm and in which the target is small. Overall, our evidence suggests that bidders benefit from sharing an auditor with the target. Our results are robust to controls for alternative explanations and for selection bias in the shared-auditor effect.